Ben is back [videorecording (DVD)] - Hedges, Peter; Roberts, Julia, 1967-; Hedges, Lucas, 1996-; Vance, Courtney B (Roadside Attractions LLC, 2019)
Ben Burns, a drug-addicted teenager, shows up unexpectedly to visit his family on Christmas Eve. His wary mother welcomes him, but after finding out he's still in danger, she must to do everything she can to help her family.